2011
DOI: 10.3329/jsr.v3i3.7049
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Vegetable Oils

Abstract: The internal structures of agricultural products change substantially in the course of the products deformation. One of the main changes in this process is the loss of the water content and water solutions generally due to the squeezing out of the cellular sap. The water content can be detected also by electric conductivity measured at different frequencies. The precise measurement of the electric conductivity during the deformation of soft agricultural products can be used as a simple indicative method for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 13 publications
5
40
0
2
Order By: Relevance
“…A característica de biodegradabilidade, alto ponto de fulgor (> 300 °C) e a possibilidade de aumentar a vida útil do papel isolante, são os pontos mais relevantes que podem ser abordados (Fofana et al, 2010). Diversos autores vêm reportando exemplos do uso de óleos vegetais como óleo isolante aplicado em transformadores de distribuição de energia, tais como óleo de palma, canola e oliva (Essam & Al-Ammar, 2010), óleo de milho e algodão (Shah & Tahir, 2011 Com base no exposto considera-se imprescindível caracterizar óleos vegetais disponíveis no Brasil, no sentido de se chegar a alternativas viáveis uma vez que, em regra, materiais comerciais apresentam segredos de preparação. Assim, o objetivo do trabalho é apresentar os resultados da investigação de características físico-químicas e dielétricas dos óleos de algodão, babaçu, girassol, milho e soja da classe comestível.…”
Section: Introductionunclassified
“…A característica de biodegradabilidade, alto ponto de fulgor (> 300 °C) e a possibilidade de aumentar a vida útil do papel isolante, são os pontos mais relevantes que podem ser abordados (Fofana et al, 2010). Diversos autores vêm reportando exemplos do uso de óleos vegetais como óleo isolante aplicado em transformadores de distribuição de energia, tais como óleo de palma, canola e oliva (Essam & Al-Ammar, 2010), óleo de milho e algodão (Shah & Tahir, 2011 Com base no exposto considera-se imprescindível caracterizar óleos vegetais disponíveis no Brasil, no sentido de se chegar a alternativas viáveis uma vez que, em regra, materiais comerciais apresentam segredos de preparação. Assim, o objetivo do trabalho é apresentar os resultados da investigação de características físico-químicas e dielétricas dos óleos de algodão, babaçu, girassol, milho e soja da classe comestível.…”
Section: Introductionunclassified
“…The relative permittivity of the mineral oil was only 2.15. The difference in relative permittivity was observed mainly due to the fact that different insulating liquids have different moisture contents, polarities, and dipole polarization (Lison et al, ; Shah and Q a, ; Zech et al, ). Rajab et al () and Wang () demonstrated that there is a correlation between the degree of polarity and relative permittivity.…”
Section: Resultsmentioning
confidence: 99%
“…Vegetable plant based natural oils possess dielectric properties comparable or even better than hydrocarbon and mineral oil based dielectrics [20]. Many researchers have experimented with natural oils as dielectric fluid for power transformers and other electrical engineering applications [21,22].…”
Section: Introductionmentioning
confidence: 99%